Synthesis and Crystal Structure of Complex [Cd(CH3COO)2(C7H6N2S)2] - Ma, Wei-Xing; Qian, Bao-Hua; Ge, Hong-Yu (Asian Journal of Chemistry, 2012)
A mixed complex [Cd(CH3COO)2(C7H6N2S)2] was synthesized based on the reaction of cadmium acetate and 2-aminobenzothiazole (C7H6N2S) in methanol medium. The structure of this complex was characterized by elemental analysis and IR spectrum. The crystal structure of the compound [Cd(CH3COO)2(C7H6N2S)2] was also determined by X-ray single crystal diffraction. The crystal belongs to crystal orthorhombic system with space group Pna2(1) and crystallographic data of the compound are: a = 0.88831(15) nm, b = 2.7449 (3) nm, c = 0.90103(16) nm, a = b = g = 90º, V = 2.1970(6) nm3; Dc = 1.605 g/cm3; Z = 4; F(000) = 1064; m = 1.214 mm-1.